Cure of mycobacterium avium keratitis caused by trauma in elderly: case report - Chen, Xiaoting; Wang, Hongyan; Wen, Kaizhen; Lin, Shuilong; Li, Bingbing; Lin, Meiying (Frontiers in Cellular and Infection Microbiology, 2023)
We report a case of Mycobacterium avium keratitis, first detected in the laboratory, which is from an 81-year-old female patient with a 13-year history of recurrent keratitis after eye injuries. This patient underwent anterior chamber irrigation of the right eye, and autologous conjunctival flap covering plus medication, and the corneal ulcer healed. She recovered well after continuing with the medication for half a year. The patient was not immune-compromised. Complex eye diseases such as blurred vision and cataracts caused by advanced age, delayed symptoms caused by slow growth of Mycobacterium avium and low-grade inflammation, difficulty with laboratory culture, repeated medication use, and repeated illnesses were the main reasons for the prolonged failure to clarify the etiology of this case. Morphological examination provided important clues for the initial discovery of pathogenic bacteria. Remind to pay attention to the morphology of Mycobacterium under Gram staining and Rui’s Giemsa staining. Acid fast staining and Deoxyribonucleic Acid(DNA) microarray chip method can be used as indicators for rapid diagnosis of Mycobacterium species.